Hadith About Capital in Education and Economics - Hafi; Ahmad Mohammad Tidjani (Penerbit Hellow Pustaka, 2024)
Islam provides guidelines regarding the values that regulate trade and economics, so that they are always in harmony with the principles in the Koran and Hadith. Islam views capital as a tool for developing businesses that can bring benefits, both in economic and educational aspects. The hadiths of the Prophet Muhammad SAW provide many clues about the importance of capital in life, both to improve individual welfare and to contribute to society. Capital in Islam is not only measured from a material perspective, but also from a scientific perspective, which is the main capital in achieving progress. This research aims to analyze the concept of capital in Islam, both in educational and economic contexts, as well as how these principles can be applied to create the benefit of the people. This research uses a qualitative approach and literary methods, this research concludes that capital used with good intentions in accordance with Islamic law can bring blessings and benefits both in this world and the hereafter.